OPIOID-FREE ANESTHESIA: SURGICAL VIEW. - Ghazi Mohammed Alotaibi,Yahya Ahmad Madkhali,Sattam Ali Alenazi,Mustafa Mohammed Oraybi,Taib Hadi Oaribi,Abdullah Turki Almutair,Hisham Mohmmed Moafa,Jameel Farhan Alruwaili; Abdullah Saad Alotaibi,Farhan Nasser Ayed,Mazyad Abdullh Al Resheedi,Muhammad Ali Hussein,Saad Ayidh Lafi Almutairi,Raed Nazzal Almutairi,Turki Magbool Alazmi,Musleh Muslim Al-Hujaili,Ahmed Mohammed Alshwaikan (Chelonian Research Foundation, 2022)
Opioid-free anesthesia (OFA) is a cutting-edge perioperative treatment strategy designed to maximize patient outcomes while reducing the negative consequences of opioid use. An extensive summary of the most recent research on OFA is given in this abstract, with special attention to the adjuvant function of dexmedetomidine (Dex). Important conclusions from numerous trials conducted in a range of surgical settings are compiled, emphasizing the advantages of OFA in lowering opiate use, and minimizing postoperative pain, nausea, and vomiting. Additionally, OFA exhibits promise in a few patient populations, such as the obese, the respiratoryly ill, and those with chronic pain; however, close observation for side effects including bradycardia and hypotension is necessary. A multimodal strategy for managing anesthesia that includes customized patient care, non-opioid analgesic drugs, regional anesthesia methods, and cutting-edge monitoring technologies is essential to the effectiveness of OFA. Even with the encouraging results, there are still issues like study heterogeneity and unsolved long-term ramifications questions. Large-scale randomized controlled trials and standardized procedures are required to provide solid proof in favor of OFA's broad use. OFA has the potential to completely transform perioperative care, increasing patient safety and improving outcomes in surgical settings with further study and cooperation. Key words: opioid-free anesthesia, dexmedetomidine, perioperative care, postoperative pain, anesthesia management, adverse effects, multimodal approach, randomized controlled trials.